Efficacy of Tailored Helicobacter pylori Eradication Treatment Based on Clarithromycin Susceptibility and Maintenance of Acid Secretion. Issue 4 (1st April 2014) - Sugimoto, Mitsushige; Uotani, Takahiro; Sahara, Shu; Ichikawa, Hitomi; Yamade, Mihoko; Sugimoto, Ken; Furuta, Takahisa
Abstract Background Insufficient acid inhibition during Helicobacter pylori eradication treatment and bacterial resistance to antibiotics often causes eradication failure. Four times daily dosing (q.i.d.) of a proton‐pump inhibitor (PPI) achieves potent acid inhibition, suggesting its potential usefulness as a regimen for eradicating H. pylori infection. Therefore, a tailored eradication regimen based on antibiotic susceptibility and maintenance of acid inhibition should have a high success rate. We investigated the efficacy of such treatment based on clarithromycin (CAM) susceptibility. Methods Using 153 H. pylori‐positive Japanese patients, we investigated the efficacy of tailored eradication strategy: (1) Patients infected with CAM‐sensitive H. pylori were treated with a PPI (rabeprazole 10 mg q.i.d.), amoxicillin 500 mg q.i.d., and CAM 200 mg b.i.d. (n = 89), and (2) patients infected with CAM‐resistant were given the same doses of rabeprazole and amoxicillin and metronidazole 250 mg b.i.d. (n = 64) for 1 week. Results In the tailored regimen group, the overall eradication rate was 96.7% (95% CI: 92.5–98.9%, 148/153) in the intention‐to‐treat (ITT) analysis and 97.4% (93.4–99.3%, 148/152) in the PP analysis. The eradication rates for the CAM‐ and metronidazole‐based treatments were similar (95.5% and 98.4%, respectively, p = .400). The tailored treatment achieved a high eradication rate in CYP2C19 rapid metabolizers who were a resistance genotype for PPI treatment (94.3% (86.0–98.4%, 66/70)). Discussion A tailored H. pylori eradication regimen based on CAM susceptibility and maintaining acid secretion (rabeprazole 10 mg q.i.d.) is useful because it can achieve an eradication rate exceeding 95%, irrespective of eradication history, thus overcoming differences among CYP2C19 genotypes.